Wage inequality, skill inequality, and employment: Evidence and policy lessons from PIAAC - Sonja Jovicic (IZA Journal of European Labor Studies, 2016)
This paper investigates international differences in wage inequality and skills and whether a compressed wage distribution is associated with high unemployment across core OECD countries. Wage dispersion and wage structure are widely debated among policymakers; compressed wage structure is often perceived as an important cause of high unemployment. Firstly, this paper examines differences in wage dispersion across OECD countries and their link to skill dispersion. Some countries that have more compressed (dispersed) wage structures simultaneously have more compressed (dispersed) skill structures as well, and skill differences explain part of the differences in wage dispersion. However, even when accounted for skills, some countries have a more compressed wage structure, most likely caused by labor market institutions. We do not find an effect of wage compression on the labor market performance in the low-skill sector. Based on the Program for International Assessment of Adult Competencies (PIAAC) survey of adult skills for core OECD countries, this paper cannot confirm the skill compression nor wage compression hypotheses. Rather than insisting on the deregulation of labor market institutions and reductions in public welfare policy as the main policy recommendations to achieve higher employment (and higher wage inequality), policymakers should reconsider aggregate demand deficiency and the variation in macroeconomic policies as potential explanations for the employment differences across countries.
Keywords: J31; J24; E24; 330; Wage distribution; Earnings; Skill distribution; Employment